Iron-Catalyzed Oxidative Coupling of Benzylamines and Indoles: Novel Approach for Synthesis of Bis(indolyl)methanes - Gopalaiah, Kovuru; Chandrudu, Sankala Naga; Devi, Alka (Synthesis, 2015)
A novel route for synthesis of bis(indolyl)methanes has been developed by the oxidative coupling of benzylamines and indoles in the presence of iron(II) triflate as a catalyst and molecular oxygen as an oxidant. This method promises versatility, cost-effectiveness, and efficiency.
Keywords: oxidative coupling; benzylamine; bis(indolyl)methane; iron(II) triflate; molecular oxygen